2018
DOI: 10.1007/s10661-018-6589-3
|View full text |Cite
|
Sign up to set email alerts
|

A robust and accurate surrogate method for monitoring the frequency and duration of combined sewer overflows

Abstract: Discharges of untreated wastewater from combined sewer overflows (CSOs) can affect hydraulic stress and have significant environmental impacts on receiving water bodies. Common flow rate and water level sensors for monitoring of CSO events are expensive in terms of investment costs, installation, operation and maintenance. This paper presents a novel surrogate method to detect CSO events by using two low-cost temperature sensors. The novelty is the experimental setup for installation of temperature sensors in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…(2013) by adding a second temperature sensor, improving the detection accuracy by implementing an algorithm that accounted for the response time of the system and automatically calculated the duration of CSO events (Hofer et al, 2018). As a result, in a 7-month test phase, all 20 CSO events were recognised without false detections.…”
Section: Innovative Methods For Cso Determinationmentioning
confidence: 99%
“…(2013) by adding a second temperature sensor, improving the detection accuracy by implementing an algorithm that accounted for the response time of the system and automatically calculated the duration of CSO events (Hofer et al, 2018). As a result, in a 7-month test phase, all 20 CSO events were recognised without false detections.…”
Section: Innovative Methods For Cso Determinationmentioning
confidence: 99%
“…A recent study introduced a rather robust and simple method to detect overflow events and record their duration (Hofer et al, 2018). This method requires two thermometers: one in the main pipe and one at the invert level of the overflow pipe: once the temperatures are equal at both sites, there is an overflow.…”
Section: Event Detectionmentioning
confidence: 99%
“…Smart stormwater systems are gaining popularity as a tool to increase the efficiency of conventional stormwater capture. These systems rely on an integrated network of sensors and control structures for real-time control (RTC) of stormwater infrastructure at a system level. , For example, smart stormwater detention ponds respond to weather forecasts by releasing stored water in advance of precipitation events. Smart systems have been developed to detect and reduce combined sewer overflows and forecast and reduce urban flood risk. Recent studies have explored the use of RTC technology to manage environmental flows, shape streamflow, and achieve multi-objective scenarios including, for example, stormwater retention and pollutant removal. ,, RTC technology also allows for the adaptation of stormwater systems to future land use changes, population growth, and climate change. ,, While the addition of RTC to a stormwater capture system cannot directly increase water supply, it can increase the volume of stormwater captured. , For example, Luthy et al . suggested that “in drought-prone regions where stormwater capture can contribute to water supply, RTC can improve both the quality and quantity of water recharged” to aquifers.…”
Section: Introductionmentioning
confidence: 99%